Design, construction and testing of an ascending micropenetrometer to measure soil crust resistance - Lorentz, Andrew (Cranfield University, 2014)
The increasing world population is putting pressure on global food production. Agriculture must meet these growing demands by increasing crop yields. One phenomenon which prevents seedling emergence and damages crop yield is soil crusting. Understanding of soil crusting and the factors which influence it is fundamental to ensuring good crop production. An instrument which will test soil crust strength in a novel way, mimicking seedling growth, may lead to pre-emptive agricultural soil management which could increase crop production. This work details the process of design, construction and testing of an ascending penetrometer to measure soil crust strength. The full design process is discussed from concept generation and evaluation, using experimental methods and a multi-criteria decision making tool, through to final design configuration, specification, manufacture and testing. Traditionally, soil penetrometers measure soil strength by forcing a probe from the surface of the soil into the bulk soil below. To more accurately measure the direct impedance a seedling would experience a device should measure impedance from the bulk soil upwards and into the soil crust, mimicking what a growing seedling would experience. Results prove that the manufactured ascending penetrometer with a force resolution of 0.01N and displacement resolution of 0.0004mm is capable of detecting differences in soil crusts. At these resolutions and accuracy to 0.1N and 0.1mm excellent repeatability was achieved. The machine is therefore a useful and realistic tool for quantitatively comparing soil crusts in soil. It is hoped that being able to compare soil crust strength will lead to improved soil management techniques.
Keywords: penetration resistance; TOPSIS; seedling emergence; instrument design